Simplify each expression. 1) \( -5-3 x+1+x \) 2) \( -4 v+10 v \) 3) \( -2-5 b+9 b \) 4) \( -4 b-8 b \) 5) \( n+3+n-9 \) 6) \( 6(5 x+8) \) 7) \( 10(10 n-6) \) 8) \( -5(x-4) \) 9) \( 4(2 n+2) \) 10) \( -6(v-8) \) 11) \( -7(5-4 a)+1 \) 12) \( -5(2-9 v)+6 v \) 13) \( 4 b-3(b-7) \) 14) \( 2(-10 x-4)+6 \) 15) \( 9 n+5(n-2) \) 16) \( -2(-7+10 a)-10(7 a-1) \) 17) \( -4(n+4)-3(4+n) \) 18) \( 5(7 x-6)-(2+9 x) \)
Real Tutor Solution
Answer
Solution
Sign in to Unlock Answers for Free!
A Learning Platform Trusted by Millions of Real Students and Teachers.
Reviewed and approved by the UpStudy tutoring team
Bonus Knowledge
Sure! Let's go through the expressions one by one and simplify them. 1) \( -5 - 3x + 1 + x = -4 - 2x \) 2) \( -4v + 10v = 6v \) 3) \( -2 - 5b + 9b = -2 + 4b \) 4) \( -4b - 8b = -12b \) 5) \( n + 3 + n - 9 = 2n - 6 \) 6) \( 6(5x + 8) = 30x + 48 \) 7) \( 10(10n - 6) = 100n - 60 \) 8) \( -5(x - 4) = -5x + 20 \) 9) \( 4(2n + 2) = 8n + 8 \) 10) \( -6(v - 8) = -6v + 48 \) 11) \( -7(5 - 4a) + 1 = -35 + 28a + 1 = 28a - 34 \) 12) \( -5(2 - 9v) + 6v = -10 + 45v + 6v = 51v - 10 \) 13) \( 4b - 3(b - 7) = 4b - 3b + 21 = b + 21 \) 14) \( 2(-10x - 4) + 6 = -20x - 8 + 6 = -20x - 2 \) 15) \( 9n + 5(n - 2) = 9n + 5n - 10 = 14n - 10 \) 16) \( -2(-7 + 10a) - 10(7a - 1) = 14 - 20a - 70a + 10 = 14 - 90a + 10 = -90a + 24 \) 17) \( -4(n + 4) - 3(4 + n) = -4n - 16 - 12 - 3n = -7n - 28 \) 18) \( 5(7x - 6) - (2 + 9x) = 35x - 30 - 2 - 9x = 26x - 32 \) Let me know if you need any further assistance!